The Learning Process of Gending Sriwijaya Dance in Class X MAN 1 Prabumulih - Tiponah, Nadila Sangon; Wardiah, Dessy; Nurdin, Nurdin (CV. Rayyan Dwi Bharata, 2022)
The STAD (Student Team Achievement Division) model means the student achievement division, STAD is the student team achievement that stimulates student collaboration through learning in groups whose members are diverse to master the skills being studied. This dance learning process focuses on the various movements of the Sriwijaya Gending Dance at MAN 1 Prabumulih. The purpose of this study was to determine how the process of learning dance in the school. The research method used by the researcher is a qualitative descriptive method to obtain data from observations, interviews, and documentation regarding